2018
DOI: 10.5114/aoms.2016.58785
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular structural and functional changes evaluated by echocardiography and two-dimensional strain in patients with sickle cell disease

Abstract: IntroductionPatients with sickle cell disease have increased left ventricular size, which is not usually accompanied by changes in systolic function indexes. We assessed echocardiographic abnormalities present in patients with sickle cell anemia (SCA) and compared echocardiographic parameters to other sickle cell diseases (OSCD).Material and methodsA blind cross-sectional study with 60 patients with SCA and 16 patients with OSCD who underwent transthoracic echocardiography was performed.ResultsEchocardiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…was retrospective, and one (Mah et al.) was experimental 15,31–43,45,47 . Most studies obtained written consent and approval through an institutional review board or ethics committee.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…was retrospective, and one (Mah et al.) was experimental 15,31–43,45,47 . Most studies obtained written consent and approval through an institutional review board or ethics committee.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies obtained written consent and approval through an institutional review board or ethics committee. Eleven studies reported that patients were in steady state at the time of myocardial strain evaluation, defined as not being in any state of crisis or experiencing an acute event, generally for a minimum of 1 month 15,32,34–37,39–42,44,47 . The remaining six studies did not indicate timing of the patients’ last crisis in relation to myocardial strain evaluation (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedirian et al, [15] in a more recent research, found no difference in LV strain between a group of patients with SCD and a group of patients with other sickle cell diseases (OSCD). However, they found 79% of the patients with SCD to have abnormal strain, which is more than that we found but with a slightly higher cutoff for normal strain.…”
Section: Journal Of Translational Internal Medicine / Jan-mar 2020 / mentioning
confidence: 95%
“…However, in this population, studies are rare and results are conflicting. [11][12][13][14][15][16] More recently, the GLS was found to be altered in a population of patients with β-thalassemia, [17,18] a hemoglobinopathy that can, in some respects, be compared with SCD.…”
Section: Journal Of Translational Internal Medicine / Jan-mar 2020 / mentioning
confidence: 99%